(untitled) (Plant Tissue Culture and Biotechnology, 2020)
Embryonic tip explants of 92 Indian soyabean and 7 advanced breeding lines derived from soaked mature seeds were inoculated and co-cultivated for 5-day with Agrobacterium strain EHA105 carrying the binary vector pCambia1305.1 containing a hygromycin and kanamycin resistance gene as plant and bacterial selectable markers, respectively. Transient expression of transgene was monitored by histochemical localization of β-glucouronidase (GUSPlus) reporter activity in transformed ET tissues. A high genetic variability for Agrobacterium-infection ranging from 3.8 to 100% was observed in the form of transient GUS expression. Five highly efficient genotypes, namely DS-228, JS 335, JS 72-44, KHSb2, and JS 72-280 with transient GUS expression of 100, 98.1, 96.5, 96 and 92%, respectively were identified. In addition, various infectivity patterns in these genotypes were observed. Genotypes with very high transient GUS expression identified in this study may improve success rate of development of transgenic soybean. Plant Tissue Cult. & Biotech. 30(2): 231-242, 2020 (December)